2004
DOI: 10.1097/00008571-200404000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic determinants of interindividual variability in bupropion hydroxylation by cytochrome P450 2B6 in human liver microsomes

Abstract: Bupropion is primarily metabolized in human liver by cytochrome P450 (CYP) 2B6, an isoform that shows high interindividual variability in expression and catalysis. The aim of this study was to identify mechanisms underlying this variability through comprehensive phenotype-genotype analysis of a well-characterized human liver bank (n = 54). There was substantial variability in microsomal bupropion hydroxylation activities (over 45-fold) and CYP2B6 protein content (over 288-fold), with excellent correlation betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(172 citation statements)
references
References 24 publications
9
159
3
1
Order By: Relevance
“…Exposure to ethanol alone, and in combination with nicotine, could increase the hepatic metabolism of CYP2B1/2 substrates thereby affecting their efficacy and/or toxicity. This may be of clinical importance for a number of drugs metabolized by CYP2B such as bupropion (Hesse et al, 2000), efavirenz (Ward et al, 2003), and cyclophosphamide (Chang et al, 1993), where alterations in plasma levels can result in altered therapeutic outcomes and toxicities (Hesse et al, 2004;Rotger et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to ethanol alone, and in combination with nicotine, could increase the hepatic metabolism of CYP2B1/2 substrates thereby affecting their efficacy and/or toxicity. This may be of clinical importance for a number of drugs metabolized by CYP2B such as bupropion (Hesse et al, 2000), efavirenz (Ward et al, 2003), and cyclophosphamide (Chang et al, 1993), where alterations in plasma levels can result in altered therapeutic outcomes and toxicities (Hesse et al, 2004;Rotger et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ethanol induces rat liver CYP2B1/2 levels, via a transcriptional mechanism, resulting in increased in vitro metabolism of nicotine in rat liver microsomes (Adir et al, 1980;Schoedel et al, 2001). Chronic nicotine treatment does not alter rat or monkey hepatic CYP2B levels (Lee et al, 2006;Miksys et al, 2000a) nor are the levels higher in human smokers (Hesse et al, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…Alterations in brain CYP levels through genetic variation or through induction by commonly used drugs such as nicotine or ethanol would result in alterations in local CYP metabolism, which may contribute to the variation seen in efficacy, interactions, side effects, and toxicities of drugs that enter and act on the CNS (Gervasini et al, 2004). For example, brain CYP2B6 protein levels are higher in smokers compared to nonsmokers (Miksys et al, 2003), whereas hepatic levels are unchanged (Hesse et al, 2004), suggesting that smokers may have different therapeutic responses or side effects to CYP2B6 substrates. The anesthetic propofol is inactivated by CYP2B6, and there is evidence that smokers require a larger dose of propofol (Lysakowski et al, 2006) and report fewer postoperative side effects (Chimbira and Sweeney, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The role of the different CYP2B6 alleles for the in vivo metabolism of drugs is still largely unknown. CYP2B6*5 (R487C) and CYP2B6*7 (Q172H, K262R and R487C) variants have been suggested to cause significantly reduced protein expression levels in human liver (Lang et al, 2001), but other studies have not confirmed this (Xie et al, 2003;Hesse et al, 2004). The CYP2B6*6 allele (Q172H and K262R) has been associated with a decreased protein expression, but higher activity using cyclophosphamide as substrate (Xie et al, 2003).…”
Section: Cyp2b6mentioning
confidence: 99%